LC–MS/MS assay for quantitation of enalapril and enalaprilat in plasma for bioequivalence study in Indian subjects. (2nd February 2017) - Halder, Dhiman; Dan, Shubhasis; Pal, Murari Mohun; Biswas, Easha; Chatterjee, Nilendra; Sarkar, Pradipta; Halder, Umesh Chandra; Pal, Tapan Kumar
Background: Enalapril (EPL) is an angiotensin-converting enzyme inhibitor for the treatment of hypertension and chronic heart failure. Enalaprilat (EPLT) is an active metabolite that contributes to the overall activity of EPL.Aim: To quantitate EPL along with its metabolite EPLT using LC–MS/MS, a bioanalytical method was developed and validated with tolbutamide in human plasma using a protein precipitation technique.Results: The sensitive and selective method has an LLOQ of 1 ng/ml with a linearity range of 1–500 ng/ml for both EPL and EPLT using 300 µl of plasma without any matrix effect.Conclusion: Linearity, specificity, accuracy, precision and stability, as well as its application to the analysis of plasma samples after oral administration of 20 mg of EPL maleate in healthy volunteers demonstrate applicability to bioavailability/bioequivalence studies. Lay abstract: The present study describes a sensitive, selective, simple, accurate and reproducible LC–MS/MS method for the simultaneous determination of both enalapril (EPL) and enalaprilat (EPLT) in human plasma. The results obtained indicate the high sensitivity of the described method for analysis of EPL and EPLT, which render this method particularly useful for pharmacokinetic or bioequivalence studies. The proposed method has been applied for the analysis of EPL and EPLT in the plasma of healthy volunteers in a single-dose pharmacokinetic study.